Optical Rashba effect in a light-emitting perovskite metasurface - Tian, Jingyi (2022)
The Rashba effect, i.e., the splitting of electronic spin-polarized bands in the momentum space of a crystal with broken inversion symmetry, has enabled the realization of spin-orbitronic devices, in which spins are manipulated by spin-orbit coupling. In optics, where the helicity of light polarization represents the spin degree of freedom for spin-momentum coupling, the optical Rashba effect is manifested by the splitting of optical states with opposite chirality in the momentum space. Previous realizations of the optical Rashba effect relied on passive devices determining the surface plasmon or light propagation inside nanostructures, or the directional emission of chiral luminescence when hybridized with light-emitting media. An active device underpinned by the optical Rashba effect is demonstrated here, in which a monolithic halide perovskite metasurface emits highly directional chiral photoluminescence. An all-dielectric metasurface design with broken in-plane inversion symmetry is directly embossed into the high-refractive-index, light-emitting perovskite film, yielding a degree of circular polarization of photoluminescence of 60% at room temperature.